Ablution Furniture for Multiple User (AFME) - Abdul Rahman, Julaila; Kamaruddin, Zumahiran; Mohd Khairi, Muhammad Azim (Kulliyah of Architecture & Environmental Design, International Islamic University Malaysia, 2019)
Many mosques in Malaysia have several different types of ablutions platform; with a seat or without a seat. The ablution platforms are designed to assist Muslim ritual activity, which are a pre-requisite before performing their 5 times prayer daily. Thus, it is important to has an ergonomic, safe and hygiene ablution platform including its furniture to ensure the effectiveness of the ablution activity. This research recommended AFME as one of the option to help the Muslim users in their ablution activity.